2015
DOI: 10.1590/s1519-99402015000200017
|View full text |Cite
|
Sign up to set email alerts
|

Probiótico na alimentação de pós-larvas de tilápias-do-nilo submetidas a desafio sanitário

Abstract: Objetivou-se avaliar o efeito da cepa probiótica Saccharomy cerevisiae na alimentação de pós-lavas de tilápias-do-nilo submetidas a desafio sanitário (fezes de ovinos). Foram selecionadas 300 pós-larvas, com média de peso e comprimentos uniformes. Os tratamentos consistiram de peixes cultivados em água limpa com ração comercial, em quantidade de 10% da biomassa, sem o uso de probiótico e peixes cultivados em água sob desafio sanitário, alimentados com ração comercial, em quantidade de 10% da biomassa e com o u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
2
0
6

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 14 publications
1
2
0
6
Order By: Relevance
“…experiments have demonstrated that several probiotics sources can be suitable for tilapia (Van Hai 2015). The results corroborated to Ferreira et al (2015) who observed that when supplementing Nile tilapia larvae with S. cerevisiae strains, after a sanitary challenge, there were no effects on these parameters between the treatments. Schwarz et al (2016) also did not observe differences in tilapia length after the use of S. cerevisiae.…”
Section: Discussionsupporting
confidence: 90%
“…experiments have demonstrated that several probiotics sources can be suitable for tilapia (Van Hai 2015). The results corroborated to Ferreira et al (2015) who observed that when supplementing Nile tilapia larvae with S. cerevisiae strains, after a sanitary challenge, there were no effects on these parameters between the treatments. Schwarz et al (2016) also did not observe differences in tilapia length after the use of S. cerevisiae.…”
Section: Discussionsupporting
confidence: 90%
“…Entre as várias definições os estudos têm uma linha de raciocínio muito próximo, culminam com a afirmação de que os probióticos são organismos vivos que são administrados por via oral e traz benefícios para a saúde do animal de interesse (Dos Santos Júnior et al, 2016;Newaj-Fyzul et al, 2014;Ibrahem, 2015;Iribarren et al, 2012;Nayak, 2010;De Melo Lima et al, 2018), e que tem demostrado grande viabilidade econômica em cultivos, com o intuído de substituir agentes nocivos antibióticos que são aplicados em elevadas concentrações discriminadamente na aquicultura (Ferreira et al, 2015;Doroteo, 2018), e que possuem grande importância em uma aquicultura sustentável e ecológica (Cornélio et al, 2013;Lazado & Ciapang, 2014b). Neste sentido, o objetivo de avaliar diferentes níveis de probiótico em dietas para pós-larvas de tilápia do Nilo.…”
Section: Introductionunclassified
“…One of the benefits of probiotic use is the better absorption of nutrients by animals (FERREIRA et al, 2015). This effect was observed in Nile tilapia autochthone probiotic, after been reared for 35 days, shown higher final weight and weekly growth (JATOBÁ & MOURIÑO, 2015), as well as Nile tilapia fed commercial probiotic mix in the diet administered for 6 weeks (STANDEN et al, 2015).…”
Section: Resultsmentioning
confidence: 82%